Building the knowledge society on the Internet sharing and exchanging knowledge in networked environments - Bolisani, Ettore, 1963- (Information Science Reference, 2008)
"In today's networked societies, a key factor of the social and economic success is the capability to exchange, transfer, and share knowledge. This book provides research on the topic providing a foundation of an emerging and multidisciplinary field"--Provided by publisher.